The Power of Positive Parenting Transforming the Lives of Children, Parents, and Communities Using the Triple P System - Sanders, M.; Mazzucchelli, Trevor (Oxford University Press, 2018)
This volume draws on the editors' experience of developing Triple P, and chapters address every aspect of the system, as well as how it can be applied to a diverse range of child and parent problems in different age groups and cultural ...